ANALISIS PENDAPATAN DAN RESIKO USAHA BUDIDAYA IKAN AIR TAWAR DI KABUPATEN BENGKULU SELATAN - Andani, Apri; Yuliarso, M Zulkarnain; Widiono, Septri (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2014)
The main objective of this study is to determine the income and financial risks of freshwater aquaculture, especially tilapia. The study was conducted in Seginim, South Bengkulu, with consideration that Seginim is an area of aquaculture centers in South Bengkulu. Samples have been taken as many as 50 tilapia farmers. Data analysis was using quantitative and qualitative models. Approach starts from the calculation of operating cost, revenue, and income, and then the study of risk analysis approached by variance analysis. The results show that the income of freshwater fish farming, tilapia in particular, is Rp 59,512,743.75 per period of production per farming unit, and the level of business risk is quite high with the number of CV more than 50% (>0,5) and it has opportunity losing of income as much as minus Rp 7,127,386.37 per period of production.